Mass Spectrometric Analysis of Sphingomyelin with N‐α‐Hydroxy Fatty Acyl Residue in Mouse Tissues. Issue 2 (30th September 2020) - Ali, Hanif; Yamashita, Ryouhei; Morishige, Jun‐ichi; Morito, Katsuya; Kakiuchi, Naoya; Hayashi, Junji; Aihara, Mutsumi; Kawakami, Ryushi; Tsuchiya, Koichiro; Tanaka, Tamotsu
Abstract: Sphingomyelin (SM) with N ‐α‐hydroxy fatty acyl residues (hSM) has been shown to occur in mammalian skin and digestive epithelia. However, the metabolism and physiological relevance of this characteristic SM species have not been fully elucidated yet. Here, we show methods for mass spectrometric characterization and quantification of hSM. The hSM in mouse skin was isolated by TLC. The hydroxy hexadecanoyl residue was confirmed by electron impact ionization‐induced fragmentation in gas chromatography–mass spectrometry. Mass shift analysis of acetylated hSM by time of flight mass spectrometry revealed the number of hydroxyl groups in the molecule. After correcting the difference in detection efficacy, hSM in mouse skin and intestinal mucosa were quantified by liquid chromatography–tandem mass spectrometry, and found to be 16.5 ± 2.0 and 0.8 ± 0.4 nmol/μmol phospholipid, respectively. The methods described here are applicable to biological experiments on hSM in epithelia of the body surface and digestive tract.